Five-Year Outcome in Stroke Patients Submitted to Thrombolysis - Machado, C (2015)
BACKGROUND AND PURPOSE: Little is known on long-term follow-up after thrombolysis in ischemic stroke patients because the majority of studies evaluated outcome at 3 to 12 months. We aimed to assess 5-year outcome after intravenous thrombolysis (IVT). METHODS: Cohort study based on the prospective registry of all consecutive ischemic stroke patients submitted to IVT in our Stroke Unit. Five-year outcome, including living settings, functional outcome, stroke recurrence, and mortality, was ascertained by telephonic interviews and additional review of clinical records. Multivariate analyses were performed to identify predictors of outcome and mortality. Excellent outcome was defined as modified Rankin scale 0 to 1. RESULTS: Five-year outcome was available for 155/164 patients submitted to IVT. At 5 years, 32.9% of patients had an excellent outcome (95% confidence interval (CI) =25.5-43.3) and mortality was 43.9% (95%CI=36.1-51.7). Increasing age (odds ratio =0.93, 95% CI =0.90-0.97) and increasing National Institute of Health Stroke Scale (NIHSS) 24 h after thrombolysis (odds ratio =0.81, 95% CI =0.74-0.90) were independently associated with a lower likelihood of an excellent 5-year outcome. Age (hazards ratio =1.07, 95% CI =1.03-1.11) and excellent functional outcome 3 months after thrombolysis (hazards ratio =0.28, 95%CI=0.12-0.66) were independently associated with mortality during follow-up. CONCLUSIONS: One third of ischemic stroke patients have excellent 5-year outcome after IVT. Younger age, lower NIHSS 24 h after IVT, and excellent 3-month functional outcome are independent predictors of excellent 5-year outcome.